THE ANALYSIS OF 8TH- GRADE STUDENTS’ WAYS OF UNDERSTANDING AND THINKING ABOUT PROBABILITY AND STATISTICS ACCORDING TO DNR-BASED METHODOLOGICAL APPROACH - Filiz YILDIZ (Fırat University, 2019)
The purpose of this study is to analyze 8th-grade students’ ways of understanding and thinking about probability and statistics through DNR-based methodological approach. In accordance to this purpose, the study was carried out in two stages. In the 1st Stage, developing data collection instruments which would be used for evaluating and identifying students’ current ways of thinking and understanding about probability and statistics was emphasized. At this stage, the study was carried out to thirty 9thgrade students who have just graduated from a middle school and who are now studying in a public high school and it lasted for six classes (240 minutes). At the end of the 1st Stage, ‘The Test of Determining Ways of Understanding and Thinking’ (TDWUT) and ‘Evaluation Form of Ways of Understanding and Thinking’ (EFWUT) were developed. During the main application which is the 2ndstage of the study, The Test of Determining Ways of Understanding and Thinking was conducted to 80 8thgrade students who are studying in a public middle school, students’ ways of understanding and thinking about probability and statistics have been determined. The data obtained in the main application (2ndStage) which lasted five classes (200 minutes) were analyzed descriptively according to Evaluation Form of Ways of Understanding and Thinking (EFWUT) which was developed in the 1stStage and then the profiles of students regarding their ways of understanding and thinking (WUTP) have been found out. In addition to this, semi-structured interviews were conducted to three students who were chosen according to the recent profiles in order to analyze ways of understanding and thinking deeply and to identify how students think in problem solving process and in which part of the problem solving process they have difficulties. During data analysis, the justification schemes which were used by students in the problem solving process were coded as external, empirical and analytical according to proof scheme model which was developed by Harel and Sowder (1998). In accordance with the data obtained, it was identified that students have ways of understanding and thinking which were classified as excellent, good, average, poor and in valid about probability and statistics and used mostly external and empirical schemes to verify their solutions in problem solving processes. Accordingly, some suggestions were made for the future researches and teaching mathematics.